The Influence of Profitability, Growth Ratio, and Firm Size on Firm Value with Stock Price as an Intervening Variable in Healthcare Sector Companies Listed on the Indonesia Stock Exchange for the 2021-2023 Period - Sri Murtiasih; Nandhita Listya Putri (Return : Study of Management, Economic and Bussines, 2025)
The rapid growth of the business world in an increasingly competitive era of globalization has made economic actors, including companies in the health sector, face increasingly fierce competition. Companies strive to increase and maximize company value to attract investors, because higher company value guarantees greater shareholder prosperity. This study aims to examine the effect of Profitability, Growth Ratio, and Company Size on Firm Value, with Stock Price as the intervening variable, in health sector companies listed on the IDX during the period 2021-2023. This study uses secondary data from the annual reports of 12 selected companies. The analysis methods used include descriptive statistical tests, measurement model evaluation and structural model evaluation. Data processing is done using the SmartPLS program. The findings show that the model used is Fit. Profitability and Share Price significantly affect Firm Value, while Growth Ratio and Firm Size do not. In addition, Share Price is not a viable intervening variable in this study.